PENGARUH TINGKAT PENDIDIKAN ORANG TUA, LINGKUNGAN SEKOLAH, SARANA & PRASARANA, DAN POLA ASUH ORANG TUA TERHADAP PRESTASI BELAJAR SISWA PADA SEKOLAH DASAR NEGERI SELAT BARU DI KABUPATEN BARITO SELATAN PROVINSI KALIMANTAN TENGAH - AGUNG HANDAYU (JURNAL KINDAI, 2023)
This study aims to determine and analyze the variables of parents' education level, school environment, facilities & infrastructure, and parenting patterns of parents on student achievement at Selat Baru State Elementary School in South Barito Regency, Central Kalimantan Province simultaneously, partially and dominantly. The research method emphasizes the distribution of questionnaires distributed to 32 respondents, namely students of the New Straits State Elementary School in South Barito Regency, Central Kalimantan Province. Data analysis techniques to find out the overall picture of the influence of the independent and dependent variables in this study, were carried out by instrument testing, classical assumption testing and multiple linear regression analysis. The three hypotheses in this study are proven and accepted that the variables of parents' education level, school environment, facilities & infrastructure, and parenting patterns have a simultaneous, partial and dominant influence on student achievement at the New Straits State Elementary School in South Barito Regency Central Kalimantan Province. Keywords: Parents' Education Level, School Environment, Facilities & Infrastructure, Parenting Patterns, Student Achievement